Understanding A and B-site engineered lead-free Ba(1−x)CaxZryTi(1−y)O3 piezoceramics: a perspective from DFT. Issue 12 (9th March 2021) - Premkumar, S.; Radhakrishnan, S.; Mathe, V. L.
Abstract : DFT has been used to investigate the structural and polarization of Ba(1-x) Cax Zry Ti(1−y) O3, perovskite solid solutions namely BaTiO3 (BT), Ba(Zr0.125 Ti0.875 )O3 (BZT), (Ba0.875 Ca0.125 )TiO3 (BCT) and Ba0.875 Ca0.125 (Zr0.125 Ti0.875 )O3 (BCZT). Abstract : Density functional theory (DFT) was used to investigate the structure and polarization of lead-free piezoelectric, Ba(1− x ) Ca x Zr y Ti(1− y ) O3, perovskite solid solutions, namely BaTiO3 (BT), Ba(Zr0.125 Ti0.875 )O3 (BZT), (Ba0.875 Ca0.125 )TiO3 (BCT) and Ba0.875 Ca0.125 (Zr0.125 Ti0.875 )O3 (BCZT). Here, we focus on understanding the effect of the simultaneous substitution of Ca and Zr in the BT lattice on structural and polarization behaviour. During the calculations a BT supercell was allowed to relax with substitution of Ca and Zr individually as well as simultaneously to obtain new atomic positions and lattice vectors. The density of states was calculated for all the compositions and the effect of Ca and Zr ions on O 2p and Ti 3d hybridization was studied along with their band gap. Berry phase calculations were performed to understand the polarization behaviour, and phonon dispersion calculations were also performed to understand the structural stability of BCZT compositions. The compositions investigated by DFT calculations were synthesised by a solid oxide route and analysed using X-ray diffraction. Structural properties were obtained using DFT analysis and Rietveld refinement of BCZT; polarization obtained using Berry phase calculations and experimentally obtained ferroelectric behaviour were compared. Further dielectric and piezoelectric properties of BCZT were studied.